Nutrition During Pregnancy and Lactation: Implications for Maternal and Infant Health - Redman, Leanne M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Pregnancy is a viewed as a window to future health. With the birth of the developmental origins of human adult disease hypothesis, research and clinical practice has turned its attention to the influence of maternal factors such as health and lifestyle surrounding pregnancy as a means to understand and prevent the inter-generational inheritance of chronic disease susceptibility. Outcomes during pregnancy have long-lasting impacts on both women on children. Moreover, nutrition early in life can influence growth and the establishment of lifelong eating habits and behaviors. This Special Issue on "Nutrition during Pregnancy and Lactation: Implications for Maternal and Infant Health" is intended to highlight new epidemiological, mechanistic and interventional studies that investigate maternal nutrition around the pregnancy period on maternal and infant outcomes. Submissions may include original research, narrative reviews, and systematic reviews and meta-analyses.